The Influence Of Financial Performance On Stock Prices In Food And Beverage Sub-Sector Companies On The Indonesian Stock Exchange - Nur Azizah; Ismail Badollahi; Amelia Rezki Septiani Amin (International Journal of Economic Research and Financial Accounting, 2024)
This research was created to find out how financial performance influences share prices in food and beverage sub-sector companies listed on the Indonesian Stock Exchange for the 2018-2022 period. The approach taken is a quantitative approach. Meanwhile, the type of data used in this research is quantitative data in the form of annual financial reports from 2018 to 2022. The sample used was 22 manufacturing companies listed on the Indonesia Stock Exchange. Data analysis techniques in this research use descriptive statistics, classical assumption tests, multiple linear regression, t test, F test and coefficient of determination. Data management in this research uses the SPSS version 26 software program. The results of this research prove that partial Return on Assets has a significant effect on stock prices. Meanwhile, Current Ratio, Debt to equity ratio and Total Asset Turnover do not have a significant effect on share prices. Simultaneously shows that the Current Ratio, Debt to equity ratio, Return on Assets and total Asset Turnover together influence stock prices.